Impact of stromal cell components of tumor microenvironment on epithelial-mesenchymal transition in breast cancer cells - Bezdenezhnykh, N.; Semesiuk, N.; Lykhova, O.; Zhylchuk, V.; Kudryavets, Y. (Experimental Oncology, 2014)
Background: Cell and tissue homeostasis results from the dynamic balance of cell – cell and cell – extracellular component crosstalk that regulates proliferation, differentiation, and apoptosis of cells as well as secretion and activation of soluble factors and/or deposition of extracellular matrix (ECM) components. Aim: The aim of the work was to study the crosstalk between tumor cells and stromal cell components using noncontact co-cultivation in vitro system. Materials and Methods: Human and rat breast cancer (BC) cell lines, normal human fibroblasts (NHF) and endothelial cells, and aspirates of bone marrow (BM) of BC patients with different clinical course of the disease (groups “Remission” (BM-R) and “Progression” (BM-P)) were used in noncontact co-cultivation system in vitro. The cell growth, expression of epithelial-mesenchymal transition (EMT) and tumor stem cell markers (E-cadherin, vimentin, CD44), Ki-67, p21 and Slug were investigated using immunocytochemical analysis. Results: Analysis of expression of E- and N-cadherin, vimentin and Slug in BC cells has shown that T-47D and MRS-T5 cells possess mesenchymal phenotype, while MCF-7 and MRS cells possess mostly epithelial phenotype with a part of cells with mesenchymal patterns. Upon noncontact co-cultivation of fibroblasts with Т-47D or MRS-Т5 cells, BC cells acquired higher proliferative activity compared to the control cells (р < 0.05) or MCF-7 and MRS cells co-cultivated with fibroblasts. Upon noncontact co-cultivation of Т-47D cells with normal fibroblasts and BM cells from BC patients from group “Progression” there were observed increased quantity of CD44+ Т-47D cells (by 26%), decreased quantity of Е-cadherin+ Т-47D cells, and appearance of vimentin-positive cells. In co-cultivation variant Т-47D + NHF + BM-R (“Remission“) the quantity of CD44+ Т-47D cells significantly decreased (р < 0.005) and E-cadherin expression remained unaltered compared to control cells. At the same time, in NHF cell population (co-cultivation variant Т-47D + NHF + BM-P) there was detected significant increase of quantity of р21+-cells (р < 0.005), cytoplasmic localization of p21, and nuclear localization of Slug. Expression of vimentin did not alter in any variant of co-cultivation. Conclusion: The new integration cell system for investigation of the mechanisms of interaction between tumor cells and the tumor microenvironment in vitro was developed. The significant changes in proliferative activity of TC dependently on its ЕМT-status were detected after their interaction with fibroblasts and endothelial cells in noncontact co-cultivation system. BM cells of BC patients had different modifying influence on TC dependent on clinical BC course. The activation of ЕМT program was revealed in TC upon noncontact co-cultivation with BM cells of BC patients with progression of the disease. Key Words: breast cancer, epithelial-mesenchymal transition, microenvironment, bone marrow, co-cultivation.